A comparison of distribution patterns in British and Irish mosses and liverworts. (June 2013) - Preston, Christopher D; Harrower, Colin A; Hill, Mark O
Abstract : We classified 747 species of British and Irish mosses into 10 clusters, based on their recorded distribution in 10×10 km grid squares (hectads). We generated the clusters in a two-stage process using the CLUSTASPEC program, the method that we had earlier used for British and Irish liverworts and hornworts. The clusters are named after the species with distributions which are most similar to those of the clusters as a whole. Clusters of widespread species ( Bryum capillare ), southern, lowland species ( Rhynchostegium confertum ), widespread calcifuges ( Pleurozium schreberi ), upland species ( Blindia acuta ), and montane calcifuges ( Kiaeria falcata ) closely match clusters recognised in the liverworts. The remaining clusters ( Tortella flavovirens, Weissia longifolia, Mnium stellare, Encalypta alpina, Mnium lycopodioides ) are less similar. The classification of mosses into 15 and 20 clusters generates additional clusters of hyperoceanic and montane mosses which also resemble liverwort clusters. The influence of calcareous bedrock has a more marked effect in determining moss distributions and, unlike the liverworts, the 10 moss clusters include one which is predominantly coastal. Mosses tend to be a less upland group than liverworts; a smaller proportion of their species have northern and western distributions and the lowland clusters are characterised by more extreme environmental conditions. As with the liverworts, geographically restricted clusters of species with predominantly Mediterranean-Atlantic, Arctic-montane and Boreo-arctic Montane world ranges include marked concentrations of threatened species, and species which are not recorded as fruiting in the British Isles.